PjBL in Academic Writing Instruction in Higher Education: Challenges, Strategies, and Synthesis of Empirical Findings - Muhammad Syaiful Nurasman; Buyung Firmansyah; Nuralamsyah Nasution (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2026)
Academic writing is a fundamental competency for university students as it serves as the main medium for logical, critical, and ethical communication of scientific ideas. However, many students still struggle with technical, structural, and motivational aspects of academic writing, indicating the need for innovative learning models that promote autonomy, collaboration, and reflection. Although project-based learning (PjBL) has been widely applied in language education, research on its effectiveness and implementation challenges in Indonesian academic writing remains limited. This study aims to analyze the application of PjBL in academic writing instruction and identify factors influencing its effectiveness. Using a narrative review guided by the population–exposure–outcome (PEO) framework, this study synthesizes ten empirical and theoretical articles published between 2020 and 2025 from Scopus, ERIC, and Google Scholar. The findings show that PjBL consistently enhances students’ academic writing skills through authentic, collaborative, and reflective learning that strengthens critical thinking, motivation, and digital literacy. However, challenges persist in pedagogical practices, psychological readiness, and institutional support. This study highlights the need for systematic instructional design, continuous scaffolding, and academic technology training for both lecturers and students to optimize PjBL implementation in Indonesian higher education. Keywords: Project-Based Learning; Academic Writing; Higher Education